2015
DOI: 10.1177/0032329215571288
|View full text |Cite
|
Sign up to set email alerts
|

Who’s Borrowing? Credit Encouragement vs. Credit Mitigation in National Financial Systems

Abstract: Households and banks have increasingly displaced non-financial businesses and governments as the primary debtors in modern capitalist economies, resulting in more severe economic cycles, increased inequality, and external macroeconomic imbalances. Yet while the trend is nearly universal among developed economies, its intensity varies a great deal from country to country. This article highlights (1) the common international causes behind the global expansion of household and financial sector debt; (2) the diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 17 publications
(20 reference statements)
0
43
0
Order By: Relevance
“…Recent research has begun to examine the connection between mortgage debt, housing markets, and the institutional heterogeneity of political economies (Schelkle, 2012b;Trumbull, 2012;Schwartz and Seabrooke, 2009;Prasad, 2013;Fuller, 2015Fuller, , 2016. For example, Prasad (2013) argues that "mortgage Keynesianism" is a core feature of the U.S. political economy, which sustains consumption by broad credit access rather than welfare provision.…”
Section: Models Of Household Debt Accumulation: Financial Inclusion mentioning
confidence: 99%
See 3 more Smart Citations
“…Recent research has begun to examine the connection between mortgage debt, housing markets, and the institutional heterogeneity of political economies (Schelkle, 2012b;Trumbull, 2012;Schwartz and Seabrooke, 2009;Prasad, 2013;Fuller, 2015Fuller, , 2016. For example, Prasad (2013) argues that "mortgage Keynesianism" is a core feature of the U.S. political economy, which sustains consumption by broad credit access rather than welfare provision.…”
Section: Models Of Household Debt Accumulation: Financial Inclusion mentioning
confidence: 99%
“…High debt levels in Scandinavia, the Netherlands and Iberian Europe undermine the "American exceptionalism" implicit in accounts which treat the U.S. mortgage market as unique (Prasad, 2013;Schwartz, 2009). Moreover, recent institutional shifts challenge accounts that rest on static institutional indicators and data from the 1990s or early 2000s (Fuller, 2015;Schwartz and Seabrooke, 2009;Andrews et al, 2011;International Monetary Fund, 2008). While illuminating in many respects, these static comparisons deemphasize recent processes of liberalization and financialization, and therefore cannot account for increasing debt of households in many European countries, nor the uniquely declining German debt.…”
Section: Models Of Household Debt Accumulation: Financial Inclusion mentioning
confidence: 99%
See 2 more Smart Citations
“…Second, Germany had more restrictive retail banking regulations, which depressed the growth in household debt between 2000 and 2008 (Mertens, 2017). Fuller (2015) recently showed that there is considerable variation in the degree to which CMEs encourage or mitigate household borrowing, either through interest rate restrictions, 400 property transfer taxation, loan-to-value regulations, mortgage interest taxation or supporting/curtailing secondary markets for consumer debt (see also Barnes 2016…”
Section: Ecb Monetary Policy and Widening Trade Imbalances (2002-2009)mentioning
confidence: 99%